Humanism: Goals, and Beliefs addressed in English Language Teaching Programs; Literature Review - Desi Yanita; Sri Sumarni (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
Humanism is a philosophical stance that highlights the value and ability of human beings. The presence of language in human existence cannot be seen in isolation or as without any purpose. Therefore, it is crucial to dig deeper the application of Humanism in English language teaching. This study explores the goals and beliefs of Humanism, presents the basic elements of ELT programs, and shows in what ways that goals and beliefs of Humanism has been addressed in ELT programs. A literature review was conducted, involving article collection, article reduction, display, discussion, and conclusions. The study found that goals and beliefs of Humanism are addressed in some English language teaching programs, for instance Communicative Language Teaching (CLT), Silent Way, Suggestopedia, Total Physical Response (TPR), Community Language Learning (CLL), and Task-Based Learning (TBLT). Moreover, it can be seen that the application of goals and beliefs may be wholly but also partly an element of a learning program. Acknowledging these, addressing Humanism in ELT program is varied, and recognizing these contributing factors can help challenge biases and fathom our knowledge of Humanism.